Flexible pavement crack's severity identification and classification using deep convolution neural network / A. Ibrahim ...[et al.] - Ibrahim, A.; M. Zukri, N. A. Z.; Ismail, B. N.; Osman, M. K.; Yusof, N. A. M.; Idris, M. (Universiti Teknologi MARA, 2021)
Effective road maintenance program is vital to ensure traffic safety, serviceability, and prolong the life span of the road. Maintenance will be carried out on pavements when signs of degradation begin to appear and delays may also lead to increased maintenance costs in the future, when more severe changes may be required. In Malaysia, manual visual observation is practiced in the inspection of distressed pavements. Nonetheless, this method of inspection is ineffective as it is more laborious, time consuming and poses safety hazard. This study focuses in utilizing an Artificial Intelligence (AI) method to automatically classify pavement crack severity. Field data collection was conducted to allow meaningful verification of accuracy and reliability of the crack's severity prediction based on AI. Several important phases are required in research methodology processes including data collection, image labelling, image resizing, image enhancement, deep convolution neural network (DCNN) training and performance evaluation. Throughout the analysis of image processing results, the image output was successfully classified using MATLAB software. The good agreement between field measurement data and DCNN prediction of crack's severity proved the reliability of the system. In conclusion, the established method can classify the crack's severity based on the JKR guideline of visual assessment.